CHEMICAL AND PHYTOCHEMICAL STUDY OF OPUNTIA FICUS-INDICA “TUNA”, AND FUNCIONAL FOOD ELABORATION - Tomás Ch., G. (2012)
We worked with the cladode, gel and pulp of the fruit: red, purple and white of Opuntia ficus-indica “tuna” in the region of Ayacucho Wari Department, Huamanga province in order to determine the presence of minerals, metabolites secondary antioxidant capacity and consider a functional food. The phytochemical screening according to the method of Cain - Bohmann determined catechic the presence of tannins, steroidal saponins, flavonoids, coumarins, and alkaloids. The total fiber content was found in the range of 0,42 to 0,68%, fat 0,01 to 0,02% protein and 0,39 to 0,57%. For analysis of nutrients as found AOAC magnesium, calcium, zinc and phosphorus, potassium and iron traces. Due to the presence of these nutrients to the tuna it can be considered as a functional food. Jams pulp obtained tunas studied were evaluated according to standard NTS MINSA No. 071 / DIGESA V.01, giving as a passing grade. The sweetness of the jam was obtained in the range of 65-70%. We found increased antioxidant capacity in red and purple prickly pears, determined by the method of Brand-Williams modified by Sandoval.